2009
DOI: 10.1088/0741-3335/51/6/065014
|View full text |Cite
|
Sign up to set email alerts
|

Electron energy distribution function, plasma potential and electron density measured by Langmuir probe in tokamak edge plasma

Abstract: The electron energy distribution function (EEDF) at different radial positions is derived from Langmuir probe measurements in the CASTOR tokamak edge plasma using the first derivative method. It is shown that the EEDFs are not Maxwellian but can be approximated as bi-Maxwellians with one dominant, low temperature electron population and one minority composed of hotter electrons. In the limiter shadow the measured EEDFs are Maxwellian. The values of the plasma potential and electron densities at different radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 22 publications
2
54
0
1
Order By: Relevance
“…An elevated non-Maxwellian tail into the plate results in an overestimate of the temperature estimation by divertor Langmuir probes by a factor of 2-6, using classical probe techniques [10,14].…”
Section: Contribution To the Mainstream Fusion Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…An elevated non-Maxwellian tail into the plate results in an overestimate of the temperature estimation by divertor Langmuir probes by a factor of 2-6, using classical probe techniques [10,14].…”
Section: Contribution To the Mainstream Fusion Researchmentioning
confidence: 99%
“…Figure 4 shows results of measurements of the EEDF obtained using first-derivative method [10] during JE on CASTOR tokamak, IPP Prague. It clearly shows the bi-Maxwellian nature of the EEDF.…”
Section: Contribution To the Mainstream Fusion Researchmentioning
confidence: 99%
“…In order to address the I-V characteristic in the region beyond the floating potential, a more comprehensive probe theory is sought. In certain circumstances, it can be shown that the non-local approach is usable [12,23,24,25].…”
Section: Theorymentioning
confidence: 99%
“…In the case of a magnetized plasma, the diffusion parameter is given as follows for a perpendicularly oriented probe [12,26]:…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation